Here they come: multiple new records of Indo-Pacific alien Mollusca in Tunisia - Antit, Mouna; Gofas, Serge (Springer, 2025)
Recent collecting along the Tunisian coast revealed the occurrence of many species of alien Mollusca, all of which had been reported in the past decades from the Levantine Sea. Baseline explorations of the Gulf of Gabès in 1982 and in the 2000s revealed that only a handful of species were then present. The new sampling in the Gulf of Gabès shows high increments of alien species associated to an algal bottom nearshore, in which non-indigenous species represent 22% of the total species identified but 70% of the total of individuals. This late arrival is interpreted as the consequence of progressive adaptation of the nonindigenous species to their novel environment which is progressively warming.
Keywords: Ecología marina; Biología marina; Moluscos; Especies exóticas invasoras; Calentamiento global; Túnez; Alien mollusca; Gulf of Gabès; Columbellidae; Secondary invasion